KALIMAT INTEROGATIF DALAM SATRIYA-SATRIYA PINANDHITA KARYA KI SURATNO - Dewi Karlina; Charlina Charlina; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to describe the formation of interrogative sentences in the Knight-warrior lil'maldhita works Ki Suratno. This study used a descriptive method with documentation. The results showed that the formation of interrogative sentences contained in Knight-warrior lil'maldhita works Ki Suratno five, namely (1) the formation of interrogative sentences requesting recognition answer